Dark pulse mode-locked laser based on aluminum zinc oxide coated D-shape fiber as saturable absorber - Nizamani, Bilal (Taylor & Francis, 2021)
We have experimentally reported aluminum zinc oxide (AZO) as a novel saturable absorber to generate a mode-locked laser operating in dark pulsed regime. The D-shaped fiber was first prepared by side polishing a single-mode fiber to the 1 dB insertion loss. The AZO was dissolved in isopropyl alcohol and then deposited onto the D-shaped fiber by drop casting method. By carefully optimizing the polarization of the cavity, a dark pulse was achieved, which remained stable within the pump power of 65.7-101.35 mW. Pulse width was 220 ns, and the pulse repetition rate was 1.85 MHz.